Temporary teachers and precarious work - Stacey, Meghan; Fitzgerald, Scott; Wilson, Rachel; McGrath-Champ, Susan; Gavin, Mihajla (New South Wales Teachers' Federation, 2023)
Meghan Stacey et al. provide a historical context to the introduction of the temporary teacher category and its implications of precariousness of work and the impact on workload and career expectations.